Pembuatan LKPD multimedia interaktif berbasis problem based learning (PBL) menggunakan aplikasi course lab pada materi usaha, energi, momentum, dan impuls SMA - Fathia Rahmi; Festiyed Festiyed; Hamdi Hamdi; Silvi Yulia Sari (PILLAR OF PHYSICS EDUCATION, 2019)
In the implementationeof physics learningi, students have difficulty in analyzing and connecting physics concepts in daily life, student worksheets or LKPD in Indonesia, which are made by teachers are taken from textbooks in schools, and the use of media in learning physics has not been implemented well. This studysaims to produce a product in the form of interactive multimedia based on Problem Based Learning (PBL) using a course lab application on work, energy, momentum, and impulse chapter valid. This research focuses on making a product in teaching materials in the form of interactive multimedia LKPD in accordance with the steps of LKPD according to the Ministry of National Education (2008). The instrument used in this study was the validity test. This validity was assessed by four validators: three physics lecturers from the Faculty of Mathematics and Natural Sciences and one physics teacher. Based on the research, a product of interactive multimedia LKPD based on Problem Based Learning (PBL) using a course lab application on work, energy, momentum, and impulse chapter that was made with steps for preparing worksheets based on the Ministry of National Education in 2008 had been produced. This product are tested to find its validity with the average value of validity are 87% and 92,78% sequentially in the very valid category.